Solving the problem of gallium contamination problem in InAlN layers in close coupled showerhead reactors. (25th March 2019) - Mrad, Mrad; Mazel, Yann; Kanyandekwe, Joel; Bouveyron, Romain; Feuillet, Guy; Charles, Matthew
Abstract: Gallium contamination is a well-known problem for InAlN layers grown in close coupled showerhead metal-organic vapor phase epitaxy reactors, and we have previously suggested a model explaining this gallium incorporation and the associated reduction in indium [Mrad, J. Cryst. Growth 507, 139 (2019)]. Here we propose the hypothesis that increasing the showerhead face temperature during GaN growth should encourage the growth of more stable GaN rather than metallic gallium, and reduce the reactions between tri-methyl indium and gallium on the showerhead. Using a hot deposition shield on the showerhead, we have confirmed this, to grow for the first time almost entirely gallium free InAlN layers in a showerhead reactor.